Observations on the Family Cyperaceae of West Bengal, India - Mitra, Sunit (Indian Forester, 2022)
The members of the Cyperaceae are commonly called as the Sedges. West Bengal possesses 189 species, 6 - subspecies, and 5 - vatiety of sedges, under 20 - genera belonging to 7 - tribes under 2 - subfamilies. Most of the Cyperaceae grows within the Asian boundaries from Western to SE Asia and up to Australia and many are fond as pan tropical and Cosmopolitan in their distribution. Comparative study of the Cyperaceae of the adjoining region of the state reveals that the state of West Bengal has a rich Sedge flora in its credits. There are 18 endemic species of the Cyperaceae reported from the state of West Bengal of which Carex is the most dominating genus with 12 - endemic species. The perusal of the altitudinal growth habit reveals that the numbers of Genera and species are gradually lowering down with the increase of altitude. Cyperus, Fimbristylis, Schoenoplectus etc. are the most important genera found to grow mostly in the plains to Middle hills region up to an altitude of 1500m. Carex is a genus which mostly inhabitant of the upper to cold temperate region of the state ranging an altitude of 2100m – 3800m.